Pengendalian Pencemaran Udara Emisi Sumber Tidak Bergerak di PT. X - Sabila Hani Putri; Natalina; Hardoyo (Fakultas Teknik Universitas Hamzanwadi, 2025)
Stationary source emissions are one of the main contributors to air pollution from the industrial sector. This internship aims to assess the application of emission control technology in boiler, dryer, and generator units at PT. X and to determine its effectiveness in meeting emission quality standards according to national regulations. The methods used include field observations, production process studies, and qualitative descriptive analysis of emission monitoring results. The results of the observations indicate that PT. X has implemented control technologies such as Dust Collectors in boilers, Cyclone Dust Exchangers in dryers, and Air Filters and Silencers in generators. In addition, the company also utilizes Green Open Spaces (GOS) to support air quality management. The application of these technologies is able to reduce the potential for pollutants before they are released into the atmosphere and the presence of GOS helps maintain air quality in the surrounding environment. The overall evaluation shows that emission parameters are in the category of meeting quality standards, so that the efforts made by PT. X are effective in maintaining air quality and supporting the company's compliance with applicable regulations.